Hepatic toll‐like receptor 4 expression is associated with portal inflammation and fibrosis in patients with NAFLD. (5th April 2014) - Vespasiani‐Gentilucci, Umberto; Carotti, Simone; Perrone, Giuseppe; Mazzarelli, Chiara; Galati, Giovanni; Onetti‐Muda, Andrea; Picardi, Antonio; Morini, Sergio
Abstract Background & Aims Notwithstanding evidences implicating the lipopolysaccharides (LPS)/toll‐like receptor‐4 (TLR4) axis in the pathogenesis of NAFLD, there are no studies aimed to characterize hepatic TLR4 expression in NAFLD patients. We aimed to analyse hepatic TLR4 expression and to verify its relationship with disease activity/evolution in NAFLD patients. Methods Liver tissue from 74 patients with NAFLD and 12 controls was analysed by immunohistochemistry (IHC) for TLR4, α–smooth muscle actin (α–SMA) and cytokeratin‐7. IHC for α–SMA was used to evaluate activation of fibrogenic cells (hepatic stellate cells and portal/septal myofibroblasts), that for cytokeratin‐7 to count hepatic progenitor cells and bile ducts/ductules, and that for CD68, in a subgroup of 27 patients, for detecting macrophages. Serum LPS‐binding protein (LBP), a sensitive marker of LPS activity, was determined in 36 patients and 32 controls. Results As confirmed by double‐labelling experiments, the highest level of TLR4 expression was observed in hepatic progenitor cells, biliary cells and portal/septal macrophages. TLR4‐positive hepatic progenitor cells and bile ducts/ductules correlated with portal/interface inflammation, activity of fibrogenic cells and fibrosis (P < 0.001). Also the score of TLR4 positivity of porto‐septal inflammatory infiltrate correlated with number of hepatic progenitor cells and bile ducts/ductules, activity of fibrogenic cells and fibrosis (P < 0.01). Serum LBP was increased in patients compared to controls (P < 0.001), and correlated with portal/interface inflammation, activity of portal/septal myofibroblasts and fibrosis (all P < 0.05). Conclusions TLR4 expression by regenerating and inflammatory cells at the porto‐septal and interface level, favoured by increased LPS activity, is associated with activation of fibrogenic cells and the degree of fibrosis.